2015
DOI: 10.1002/chem.201501918
|View full text |Cite
|
Sign up to set email alerts
|

Co2+@Mesoporous Silica Monoliths: Tailor‐Made Nanoreactors for Confined Soft Chemistry

Abstract: Mesoporous silica monoliths with various ordered nanostructures containing transition metal M(2+) cations in variable amounts were elaborated and studied. A phase diagram depicting the different phases as a function of the M(2+) salt/tetramethyl orthosilicate (TMOS) and surfactant P123/TMOS ratios was established. Thermal treatment resulted in mesoporous monoliths containing isolated, accessible M(2+) species or condensed metal oxides, hydroxides, and salts, depending on the strength of the interactions betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(40 citation statements)
references
References 40 publications
2
38
0
Order By: Relevance
“…The final material is composed of CoFe PBA nanoparticles (3-4 nm) wrapped in surfactant molecules within the MSU-type silica channels. [58] A different approach was used to prepare CoFe, [59,69] RbCoFe, [39,59,61,69,70] NiCr [59] and NiFe [70] PBA nanoparticles within the surfactant-free ordered mesopores of silica monoliths exhibiting 2D hexagonal, cubic, lamellar and wormlike organizations. Here the solvated metal ion PBA precursor is introduced within the silica channels during the synthesis of the silica matrix.…”
Section: Two-step Introduction Of the Precursorsmentioning
confidence: 99%
See 2 more Smart Citations
“…The final material is composed of CoFe PBA nanoparticles (3-4 nm) wrapped in surfactant molecules within the MSU-type silica channels. [58] A different approach was used to prepare CoFe, [59,69] RbCoFe, [39,59,61,69,70] NiCr [59] and NiFe [70] PBA nanoparticles within the surfactant-free ordered mesopores of silica monoliths exhibiting 2D hexagonal, cubic, lamellar and wormlike organizations. Here the solvated metal ion PBA precursor is introduced within the silica channels during the synthesis of the silica matrix.…”
Section: Two-step Introduction Of the Precursorsmentioning
confidence: 99%
“…These species are hydroxylated to a certain extent, and most of the metal ions homogeneously decorate the silica walls as mononuclear hydroxylated species. [69] The second PBA precursor is then introduced into the mesopores by a simple impregnation process with use of an acidic (in order to reprotonate the metal species if necessary) aqueous solution. The formation of the PBA particles within the silica channels results from the introduction of the first PBA precursor during the monolith preparation and the subsequent introduction of the second precursor through a classical impregnation step.…”
Section: Two-step Introduction Of the Precursorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Delahaye et al showed that depending on the interaction strength between the metal species and the ethylene oxide units of P123, the ordered mesoporous silica monoliths containing remote, accessible M 2+ species, condensed metal oxides, hydroxides, or salts could be tuned. This approach opens new way for designing MSM NPs with multifunctional properties …”
Section: Fabrication Of a Mesoporous Sensing Interfacementioning
confidence: 99%
“…described very recently another interesting approach. They prepared blue silica‐based monolith from a mixture of tetramethylorthosilicate, Pluronic 123 (polyethylene polypropylene polyethylene triblock copolymer porogen), nitric acid, and cobalt nitrate (Scheme ) . This monolith was then impregnated with a solution of 1,3,5‐benzenetricarboxylic acid dissolved in ethylene glycol‐methanol‐water mixture and heated to 150°C for 3 h during which time the color changed to light pink.…”
Section: Heterogeneous Catalysismentioning
confidence: 99%